Global sensitivity analysis for hybrid membrane-cryogenic post combustion carbon capture process - Norfamila, Binti Che Mat; Lipscomb, Glenn Glenn (Elsevier Ltd, 2019)
Hybrid membrane-cryogenic processes can offer more cost-effective solutions to carbon dioxide (CO2) capture from a fossil fuel power plant than either membrane processes or cryogenic processes alone. Concentration of CO2 in the flue gas through membrane permeation prior to cryogenic condensation reduces the nitrogen (N2) that must be cooled and associated capital and operating costs. Moreover, the cost of membrane pre-concentration can be reduced by using the feed air to the power plant as a sweep in the stripping stage of the membrane process. (Merkel et al., 2010). The trade-off that exists between CO2 permeability and CO2/N2 selectivity constrains the materials that are available for the hybrid process and limits performance. The design variables associated with the entire process are examined here to find the design that minimizes Levelized Cost of Electricity (LCOE). Membrane transport properties are taken from points that lie on the upper bound for polymeric materials while cryogenic conditions are varied over a range that allows fulfilment of capture targets. The results indicate that variations of cryogenic condensation conditions simultaneously with membrane properties and operating conditions enables further cost reductions and leads to viable designs that balance operating and capital costs.